2016
DOI: 10.5740/jaoacint.16-0149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cultivation Conditions, Ethylene Treatment, and Postharvest Storage on Selected Quality and Bioactivity Parameters of Kiwifruit “Hayward” Evaluated by Analytical and Chemometric Methods

Abstract: Organic, semiorganic, and conventional "Hayward" kiwifruits, treated with ethylene for 24 h and stored during 10 days, were assessed by UV spectrometry, fluorometry, and chemometrical analysis for changes in selected characteristics of quality (firmness, dry matter and soluble solid contents, pH, and acidity) and bioactivity (concentration of polyphenols via Folin-Ciocalteu and p-hydroxybenzoic acid assays). All of the monitored qualitative parameters and characteristics related to bioactivity were affected ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Diseased fruit release infection-induced C 2 H 4 , which may in turn prompt ripening and feedback regulation of C 2 H 4 production in healthy contiguous kiwifruits. In the context of postharvest management, the positive effect of treating kiwifruit by low temperatures (Günther et al, 2015; Park et al, 2015b; Minas et al, 2016), with exogenous ozone (Minas et al, 2012, 2014; Tanou et al, 2015), sodium nitroprusside (Tanou et al, 2015), 1-methylcyclopropene (Mworia et al, 2012; Park et al, 2015a; Thongkum et al, 2018), acetylsalicylic acid (Zhang et al, 2003), C 2 H 4 (Hu et al, 2016; Minas et al, 2016; Park et al, 2016) and propylene (Asiche et al, 2016, 2018), or a combination of them (Minas et al, 2014, 2016; Tanou et al, 2015) was assessed, although the latter procedures have found a partial diffusion in kiwifruit industry due to their technology costs. Nevertheless, these studies provided important information on the effect of the application of these postharvest treatments on fruit firmness, respiration, acidity, shelf-life and decay, as well as on ethylene, soluble solid, reducing sugar, starch, antioxidant, and volatile compound content.…”
Section: Introductionmentioning
confidence: 99%
“…Diseased fruit release infection-induced C 2 H 4 , which may in turn prompt ripening and feedback regulation of C 2 H 4 production in healthy contiguous kiwifruits. In the context of postharvest management, the positive effect of treating kiwifruit by low temperatures (Günther et al, 2015; Park et al, 2015b; Minas et al, 2016), with exogenous ozone (Minas et al, 2012, 2014; Tanou et al, 2015), sodium nitroprusside (Tanou et al, 2015), 1-methylcyclopropene (Mworia et al, 2012; Park et al, 2015a; Thongkum et al, 2018), acetylsalicylic acid (Zhang et al, 2003), C 2 H 4 (Hu et al, 2016; Minas et al, 2016; Park et al, 2016) and propylene (Asiche et al, 2016, 2018), or a combination of them (Minas et al, 2014, 2016; Tanou et al, 2015) was assessed, although the latter procedures have found a partial diffusion in kiwifruit industry due to their technology costs. Nevertheless, these studies provided important information on the effect of the application of these postharvest treatments on fruit firmness, respiration, acidity, shelf-life and decay, as well as on ethylene, soluble solid, reducing sugar, starch, antioxidant, and volatile compound content.…”
Section: Introductionmentioning
confidence: 99%
“…Diseased fruit release infection-induced C 2 H 4 , which may in turn prompt ripening and feedback regulation of C 2 H 4 production in healthy contiguous kiwifruits. In the context of postharvest management, the positive effect of treating kiwifruit by low temperatures (Günther et al, 2015;Park et al, 2015b;Minas et al, 2016), with exogenous ozone (Minas et al, 2012(Minas et al, , 2014Tanou et al, 2015), sodium nitroprusside (Tanou et al, 2015), 1-methylcyclopropene (Mworia et al, 2012;Park et al, 2015a;Thongkum et al, 2018), acetylsalicylic acid (Zhang et al, 2003), C 2 H 4 (Hu et al, 2016;Minas et al, 2016;Park et al, 2016) and propylene (Asiche et al, 2016(Asiche et al, , 2018, or a combination of them (Minas et al, 2014(Minas et al, , 2016Tanou et al, 2015) was assessed, although the latter procedures have found a partial diffusion in kiwifruit industry due to their technology costs. Nevertheless, these studies provided important information on the effect of the application of these postharvest treatments on fruit firmness, respiration, acidity, shelf-life and decay, as well as on ethylene, soluble solid, reducing sugar, starch, antioxidant, and volatile compound content.…”
Section: Introductionmentioning
confidence: 99%